THE ROLE OF HEALTH PROMOTION IN PREVENTING DIARRHEA IN INDONESIA: LITERATURE REVIEW - Waluyo, Budi; Tosepu, Ramadhan (Preventif Journal, 2024)
ABSTRACT Health promotion in general is any planned effort to influence other people, whether individuals, groups or communities, so that they do what is expected by the perpetrators of education or health promotion. The method used in this research is a literature review by searching for relevant articles from electronic databases (Google Scholar). Health Promotion can use various media such as puns, video media and posters, leaflets, flipbooks and booklets. The research results showed that there was an increase in the knowledge of counseling participants. Before being given counseling, only 20% of participants had good knowledge about how to behave in a clean and healthy lifestyle (PHBS) in an effort to prevent diarrhea. Then there is a significant influence of health education using video and poster media, leaflets , flipbooks , booklets on children's knowledge and attitudes in preventing diarrheal diseases. Health promotion cannot be separated from the media because through the media, the messages conveyed can be more interesting and understood, so that the target can learn the message and the target can decide to adopt positive behavior. Diarrhea is a disease syndrome characterized by changes in the shape and consistency of stool, slowing down to liquefaction, as well as an increase in the frequency of defecation from usual, up to 3 or more times a day. Health promotion can use various media such as puns, video media and posters, leaflets, flipbooks and booklets. Keywords :Diarrhea; health promotion, preventing, literature review